[Libros] - Klein, Richard (2006)
Sobre la publicación en francés del libro 'Testament' de Frank Lloyd Wright, traducido y presentado por <Massu, Claude>.
Keywords: WRIGHT, FRANK LLOYD; LIBROS; ARQUITECTURA; HISTORIA; SIGLO XX